Relationship of Udder Morphometric Traits to Mothering Ability of Landrace X Large White Primiparous Sows - J. M. Dominguez; J. E. S. Manzanero; C. A. Lontoc-Junsay; P. P. Sangel (Tropical Animal Science Journal, 2020)
The use of udder morphometry is often neglected during the selection of replacement gilts. This study was aimed to characterize the udder morphometry of primiparous Landrace x Large White sows across different production stages; and to show its relationship to some mothering ability traits. A total of 20 primiparous Landrace x Large White sows were bred. For each sow, the udder morphometry was characterized by measuring traits like teat tip diameter (DIA), teat length (LEN), inter-teat distance on the same row (SAMER), adjacent teat base distance on opposite row (OPPR), and teat tip to floor distance (FLO) during pre-breeding, post-breeding, and post-farrowing stages. A comparison of observed traits was also made between left and right udders as well as between anterior and posterior udders. Furthermore, the relationship between mothering ability and udder morphometry was evaluated using correlation and regression analyses. Across stages, udder traits were symmetric; however, higher values were measured for traits in posterior than in anterior udders. In the pre-breeding stage, OPPR and FLO of the anterior part had moderate negative correlations to average weaning weight (AWWt) and average daily gain (ADG). On the other hand, in the post-breeding stage, OPPR of the posterior part had a moderate positive correlation to litter size born alive (LSBA) but had a moderate negative correlation to average birth weight (ABWt). Furthermore, IgG content in the colostrum had a strong positive correlation to SAMER of the anterior part but had a strong negative correlation to FLO of the anterior part. It can be concluded that the pre-breeding combined with post-breeding udder morphometry measurements in gilts is useful as a predictor of sow mothering ability. These traits can be included in the criteria when selecting replacement gilts to enhance the productivity of sow herd.